2009
DOI: 10.1038/nsmb.1680
|View full text |Cite
|
Sign up to set email alerts
|

A two-pronged strategy to suppress host protein synthesis by SARS coronavirus Nsp1 protein

Abstract: Severe acute respiratory syndrome coronavirus nsp1 protein suppresses host gene expression, including type I interferon production, by promoting host mRNA degradation and inhibiting host translation, in infected cells. We present evidence that nsp1 uses a novel, two-pronged strategy to inhibit host translation/gene expression. Nsp1 bound to the 40S ribosomal subunit and inactivated the translational activity of the 40S subunits. Furthermore, the nsp1-40S ribosome complex induced the modification of the 5'-regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
512
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 377 publications
(548 citation statements)
references
References 41 publications
24
512
1
Order By: Relevance
“…A subsequent BCoV DI RNA mutagenesis study further suggested that this multipartite RNA structure may involve several stem-loop (sub)structures identified in earlier studies (Gustin et al, 2009;Raman and Brian, 2005) but require refolding of other RNA structures suggested earlier to be essential for DI RNA replication (Brown et al, 2007). The study by Su et al (2014) also identified an intriguing requirement in cis of an oligopeptide sequence in the Nproximal part of nsp1, suggesting that nsp1 may be an essential cis-acting protein factor in betacoronavirus replication, in addition to its multiple other functions (Brockway and Denison, 2005;Huang et al, 2011a,b;Kamitani et al, 2006Kamitani et al, , 2009Lei et al, 2013;Lokugamage et al, 2012;Narayanan et al, 2008a;Tanaka et al, 2012;Tohya et al, 2009;Wathelet et al, 2007;Züst et al, 2007). Possible interacting partners for nsp1 remain to be identified.…”
Section: Functional and Structural Features Of Coronavirus 5 Cis-actimentioning
confidence: 91%
“…A subsequent BCoV DI RNA mutagenesis study further suggested that this multipartite RNA structure may involve several stem-loop (sub)structures identified in earlier studies (Gustin et al, 2009;Raman and Brian, 2005) but require refolding of other RNA structures suggested earlier to be essential for DI RNA replication (Brown et al, 2007). The study by Su et al (2014) also identified an intriguing requirement in cis of an oligopeptide sequence in the Nproximal part of nsp1, suggesting that nsp1 may be an essential cis-acting protein factor in betacoronavirus replication, in addition to its multiple other functions (Brockway and Denison, 2005;Huang et al, 2011a,b;Kamitani et al, 2006Kamitani et al, , 2009Lei et al, 2013;Lokugamage et al, 2012;Narayanan et al, 2008a;Tanaka et al, 2012;Tohya et al, 2009;Wathelet et al, 2007;Züst et al, 2007). Possible interacting partners for nsp1 remain to be identified.…”
Section: Functional and Structural Features Of Coronavirus 5 Cis-actimentioning
confidence: 91%
“…In addition to the nsps mentioned above, other CoV nsps are involved in RNA binding (nsp9 and nsp10; [48,49]) or in evasion of the antiviral response of the host (nsp1 and nsp3; [50,51,52,53,54,55,56,57]). The function of nsp2 is not yet known, although this protein was shown not to be essential for virus replication [58,59].…”
Section: Coronavirus Nonstructural Proteinsmentioning
confidence: 99%
“…This 'host shutoff' phenotype can be triggered through a range of mechanisms that operate at nearly every stage of the gene expression cascade. Viruses whose host shutoff strategies involve the induction of widespread mRNA decay include the alpha and gammaherpesviruses, vaccinia virus (VACV), influenza A virus (IAV), and SARS coronavirus (SCoV) [1][2][3][4][5] In each of the above cases, mRNA degradation is induced via one or more internal endonucleolytic cleavages in the target mRNA or, in the case of VACV, direct removal of the mRNA 5' cap [5][6][7][8][9]. This is invariably followed by exonucleolytic degradation of the cleaved fragment(s) by components of the mammalian RNA decay machinery such as Xrn1 [1,10,11].…”
Section: Introductionmentioning
confidence: 99%